2007
DOI: 10.1200/jco.2007.11.4769
|View full text |Cite|
|
Sign up to set email alerts
|

Prostate-Specific Antigen and Pain Surrogacy Analysis in Metastatic Hormone-Refractory Prostate Cancer

Abstract: In the TAX327 trial, a PSA decline of > or = 30% within 3 months of chemotherapy initiation had the highest degree of surrogacy for overall survival, confirming data from the Southwest Oncology Group 9916 trial. However, given the wide CIs around the estimate of this moderate surrogate effect, overall survival should remain the preferred end point for phase III trials of cytotoxic agents in HRPC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
147
5
2

Year Published

2008
2008
2016
2016

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 257 publications
(163 citation statements)
references
References 18 publications
8
147
5
2
Order By: Relevance
“…Visceral metastasis, performance status, pain, and hemoglobin and alkaline phosphatase levels were proposed as prognostic parameters for overall survival in the TAX327 study. 25,26 We demonstrated that the presence of intraductal carcinoma of the prostate on needle biopsy was the strongest prognostic parameter for cancer-specific survival and overall survival among previously reported parameters, including clinical parameters, in patients with distant metastasis at initial diagnosis.…”
Section: Discussionmentioning
confidence: 76%
“…Visceral metastasis, performance status, pain, and hemoglobin and alkaline phosphatase levels were proposed as prognostic parameters for overall survival in the TAX327 study. 25,26 We demonstrated that the presence of intraductal carcinoma of the prostate on needle biopsy was the strongest prognostic parameter for cancer-specific survival and overall survival among previously reported parameters, including clinical parameters, in patients with distant metastasis at initial diagnosis.…”
Section: Discussionmentioning
confidence: 76%
“…1 Survival of men with castrationresistant metastatic prostate cancer (CRPC) can range from several months to several years. 2,3 However, current prognostic models in CRPC only account for approximately 70% of the explained variability in survival outcomes and natural history of this disease, indicating that additional prognostic factors are likely implicated in prostate cancer outcomes. [3][4][5] There is a growing prevalence of obesity in the United States and worldwide.…”
Section: Introductionmentioning
confidence: 99%
“…21 The authors showed that the more criteria that were met for progression, the lower the rate of post-progression survival. A survival advantage to continuing chemotherapy was suggested for those men who had pain progression only.…”
Section: Progression-free Survival and Time To Progressionmentioning
confidence: 99%